Reflection XXII from Education and the Arts in the COVID-19 Era - Chomsky, Noam (Communiars. Revista de Imagen, Artes y Educación Crítica y Social, 2020)
The audiovisual document entitled "Noam Chomsky: Coronavirus - what is at stake?" is an interview with the thinker and linguist Noam Chomsky, a world reference of critical thought in the contemporary world. This conversation with Strecko Horvat, philosopher and co-founder of DiEM25 (Democracy in Europe Movement 2025), is a reflective dialogue on the pandemic situation occurring in our contexts.